DESIGN OF ANTICLIMBER COMPONENT FOR PASSIVE SAFETY SYSTEMS IN METRO KAPSUL - Patrik, Johanes
Metro kapsul, as public transportation, should protect passengers. One of strategies is to fulfill the requirements set by the government, specifically PM Transportation 175 of 2015 and SNI 8826:2019. PM Transportation 175 of 2015 explained that metro capsules require passive safety equipment and SNI8826:2019 explained that anticlimber is one of the passive safety equipments to reduce the risk of overriding when a collision occurs. Anticlimber design was carried out in this study. The design process begins with made design requirements referring to SNI 8826:2019 and continued with the preparation of anticlimber alternatives. One alternative is selected by trade off study. Then the collision simulation is carried out following SNI 8826:2019. Simulations were also carried out to review the function of the anti-climber to reduce the vertical displacement that occurs during a collision. The simulation results show that the anti-climber design can reduce the possibility of overriding. The vertical displacement of the capsule's metro wheels is reduced when an anti-climber is applied. The design of the anticlimber with c-channel profile has been designed in accordance with SNI 8826: 2019. From the simulation results, vertical displacement of the wheels of the metro kapsul occurs when the collision meets these standards.